Hierarchical Magnetic Network Constructed by CoFe Nanoparticles Suspended Within “Tubes on Rods” Matrix Toward Enhanced Microwave Absorption - Xu, Chunyang; Wang, Lei; Li, Xiao; Qian, Xiang; Wu, Zhengchen; You, Wenbin; Pei, Ke; Qin, Gang; Zeng, Qingwen; Yang, Ziqi; Jin, Chen; Che, Renchao (Nano-micro letters, 2021)
Highlights Three-dimension hierarchical core–shell Mo 2 N@CoFe@C/CNT composites were successfully constructed via a fast MOF-based ligand exchange strategy. Abundant magnetic CoFe nanoparticles suspended within “nanotubes on microrods” matrix exhibited strong magnetic loss capability, confirmed by off-axis electron holography. Hierarchical Mo 2 N@CoFe@C/CNT composites displayed remarkable microwave absorption value of − 53.5 dB. Hierarchical magnetic-dielectric composites are promising functional materials with prospective applications in microwave absorption (MA) field. Herein, a three-dimension hierarchical “nanotubes on microrods,” core–shell magnetic metal–carbon composite is rationally constructed for the first time via a fast metal–organic frameworks-based ligand exchange strategy followed by a carbonization treatment with melamine. Abundant magnetic CoFe nanoparticles are embedded within one-dimensional graphitized carbon/carbon nanotubes supported on micro-scale Mo 2 N rod (Mo 2 N@CoFe@C/CNT), constructing a special multi-dimension hierarchical MA material. Ligand exchange reaction is found to determine the formation of hierarchical magnetic-dielectric composite, which is assembled by dielectric Mo 2 N as core and spatially dispersed CoFe nanoparticles within C/CNTs as shell. Mo 2 N@CoFe@C/CNT composites exhibit superior MA performance with maximum reflection loss of − 53.5 dB at 2 mm thickness and show a broad effective absorption bandwidth of 5.0 GHz. The Mo 2 N@CoFe@C/CNT composites hold the following advantages: (1) hierarchical core–shell structure offers plentiful of heterojunction interfaces and triggers interfacial polarization, (2) unique electronic migration/hop paths in the graphitized C/CNTs and Mo 2 N rod facilitate conductive loss, (3) highly dispersed magnetic CoFe nanoparticles within “tubes on rods” matrix build multi-scale magnetic coupling network and reinforce magnetic response capability, confirmed by the off-axis electron holography.